Linear and nonlinear dynamic conductivity of carbon nanotubes - Kamal, Marzuk M; Y evthshenko, Oleg M (BRAC University, 2010)
Electronic properties of carbon nanotubes are studied. L inear response of dynamic conductivity of both zigzag and armchair nanotubes is analyzed at different temperatures and for different radii of nanotubes in the framework of semiclassical theory. Simpliˇ ed approach is used by introducing the momentum independent relaxation time approximation. At the second stage, the nonlinear response of semiconducting zigzag carbon nanotubes is studied within the same framework. I t is found that the third order response of dynamic conductivity diverges logarithmically with the increase in the radius of Carbon Nanotube. Analytic proof of this result is presented. The validity of the application of semiclassical theory for studying the nonlinear electronic properties of carbon nanotubes is discussed.